Marketing Strategy for Rennika Studio (The Indonesian Journal of Business Administration, 2015)
Abstract - Creative industry has become one of the biggest supporter for national income for growth and develop country. In Indonesia, creative industry continuously contributed to increasing income each year. One of the creative industry product is clip art. Clip art is ready made art, designs, graphics, and photographs that come bundled with illustration software packages. Today, clip art is used for printable items, like printable greeting cards, printable planner and printable calendar. For printable items, more pricey than the ordinary clip art. Rennika Studio is a small business that sells clip art and printable items, started in January 2013. Rennika sells their products at Etsy.com, an online sales site. Rennika sales demonstrated a significant drop of 25% in February 2014. The root cause of the sales decline is less product variation, have no marketing activities and owner had experienced saturated.To solve the business issue, analysis about internal and external factors is needed. External factor analysis consists of Porter’s Five Forces and Competitor Analysis, while STP and Marketing Mix 4P are used to analyze internal factor. In addition, the result of interview with the owner and customers of Rennika Studio becomes one of sources in listing SWOT of Rennika Studio. From SWOT result, TOWS matrix is utilized to generate some alternative marketing strategies for Rennika Studio. There are 12 proposed marketing strategies for Rennika Studio which are formulated into marketing mix 4P. Some of these strategies has been implemented by Rennika Studio started December 2014, the strategies are creating new product with ethnic theme, make promotion through social media, make website for Rennika, and also accept special customized order from customer. After doing the strategies, by January 2015 Rennika already enjoyed a sales increase of 15%. This progress encourages Rennika to grow her business further. Hopefully Rennika can double and differentiate her products further and start to implement the other strategies that can give more advantages for Rennika.Keywords: Marketing Strategy, Creative industry, Clip art, Printable product